1999
DOI: 10.1128/mcb.19.2.1144
|View full text |Cite
|
Sign up to set email alerts
|

Seven Novel Methylation Guide Small Nucleolar RNAs Are Processed from a Common Polycistronic Transcript by Rat1p and RNase III in Yeast

Abstract: Through a computer search of the genome of the yeast Saccharomyces cerevisiae, the coding sequences of seven different box C/D antisense small nucleolar RNAs (snoRNAs) with the structural hallmarks of guides for rRNA ribose methylation have been detected clustered over a 1.4-kb tract in an inter-open reading frame region of chromosome XIII. The corresponding snoRNAs have been positively identified in yeast cells. Disruption of the nonessential snoRNA gene cluster specifically suppressed the seven cognate rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
114
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 61 publications
2
114
0
3
Order By: Relevance
“…In addition to its role in processing the pre-rRNA, Rnt1p is required for the processing of the dicistronic snR190-U14 precursor, as well as several other snoRNAs (Chanfreau et al+, 1998a(Chanfreau et al+, , 1998bQu et al+, 1999)+ In the absence of Rnt1p, U14 is present as the unprocessed snR190-U14 transcript (Chanfreau et al+, 1998b; this work) and may well not be fully active+ Genetic depletion of U14 blocked pre-rRNA cleavage at sites A 1 and A 2 , while cleavage at site A 0 was delayed FIGURE 6. Effects of loss of Rnt1p on the 5+8S rRNA processing pathways+ Strains were grown as described for Figure 3+ RNA was extracted from RNT1 and rnt1⌬ sister strains grown at 25 8C or following transfer to 37 8C for the times indicated+ The ratios of the steady-state levels of 5+8S S :5+8S L and of the primer extension stops B1 S :B1 L were quantified with a PhosphorImager (Molecular Dynamics) and the values obtained are indicated+ A: RNA was separated on a 6% polyacrylamide gel and analyzed by Northern hybridization with oligo 015 against the mature 5+8S rRNA species+ Two forms of the mature 5+8S rRNAs, 5+8S S and 5+8S L , are indicated+ B: RNA was analyzed by primer extension using oligo 013+ I: primer extension stop at A 3 + II: primer extension stops at B1 L and B1 S + Note that the exposure shown for I is approximately fivefold longer than for II+ (Li et al+, 1990), and the inhibition of synthesis of mature U14 in the rnt1-⌬ strain may contribute to the delay in the early pre-rRNA processing reactions+ Rnt1p was also reported to be involved in the formation of 39 end of the spliceosomal snRNAs, U1, U2, and U5 (Chanfreau et al+, 1997;Abou Elela & Ares, 1998;Seipelt et al+, 1999)+ However, no defect in the splicing of the actin pre-mRNA was observed in the rnt1-⌬ strains (data not shown)+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in processing the pre-rRNA, Rnt1p is required for the processing of the dicistronic snR190-U14 precursor, as well as several other snoRNAs (Chanfreau et al+, 1998a(Chanfreau et al+, , 1998bQu et al+, 1999)+ In the absence of Rnt1p, U14 is present as the unprocessed snR190-U14 transcript (Chanfreau et al+, 1998b; this work) and may well not be fully active+ Genetic depletion of U14 blocked pre-rRNA cleavage at sites A 1 and A 2 , while cleavage at site A 0 was delayed FIGURE 6. Effects of loss of Rnt1p on the 5+8S rRNA processing pathways+ Strains were grown as described for Figure 3+ RNA was extracted from RNT1 and rnt1⌬ sister strains grown at 25 8C or following transfer to 37 8C for the times indicated+ The ratios of the steady-state levels of 5+8S S :5+8S L and of the primer extension stops B1 S :B1 L were quantified with a PhosphorImager (Molecular Dynamics) and the values obtained are indicated+ A: RNA was separated on a 6% polyacrylamide gel and analyzed by Northern hybridization with oligo 015 against the mature 5+8S rRNA species+ Two forms of the mature 5+8S rRNAs, 5+8S S and 5+8S L , are indicated+ B: RNA was analyzed by primer extension using oligo 013+ I: primer extension stop at A 3 + II: primer extension stops at B1 L and B1 S + Note that the exposure shown for I is approximately fivefold longer than for II+ (Li et al+, 1990), and the inhibition of synthesis of mature U14 in the rnt1-⌬ strain may contribute to the delay in the early pre-rRNA processing reactions+ Rnt1p was also reported to be involved in the formation of 39 end of the spliceosomal snRNAs, U1, U2, and U5 (Chanfreau et al+, 1997;Abou Elela & Ares, 1998;Seipelt et al+, 1999)+ However, no defect in the splicing of the actin pre-mRNA was observed in the rnt1-⌬ strains (data not shown)+…”
Section: Discussionmentioning
confidence: 99%
“…Yeast Rnt1p was identified by sequence homology to bacterial RNase III (Abou Elela et al+, 1996)+ Rnt1p is a double-strand specific ribonuclease that is required for the synthesis of several small nucleolar RNAs (snoRNAs) from large precursors (Chanfreau et al+, 1998a(Chanfreau et al+, , 1998bQu et al+, 1999) and for 39 end maturation of the U1, U2, and U5 small nuclear RNAs (snRNAs) (Chanfreau et al+, 1997;Abou Elela & Ares, 1998;Seipelt et al+, 1999)+ The initial functions reported for yeast Rnt1p were, however, in the processing of the prerRNA (Abou Elela et al+, 1996)+ The eukaryotic 18S, 5+8S, and 25S/28S rRNAs are transcribed as a single precursor molecule that undergoes complex posttranscriptional processing to remove the external transcribed spacers (59 ETS and 39 ETS) and internal transcribed spacers (ITS1 and ITS2)+ This process involves several exonucleolytic and endonucleolytic steps Fig+ 1B) and is largely carried out in the nucleolus+ The two earliest processing events, in the 39 ETS and at site A 0 in the 59 ETS, were reported to be inhibited in a temperature-sensitive rnt1-1 strain in vivo (Abou Elela et al+, 1996)+ In addition, model 39 ETS and 59 ETS substrates comprising stem-loop structures were specifically cleaved in vitro by the recombinant GST-Rnt1p fusion protein+ This strongly suggested that Rnt1p directly cleaved these two sites+ Since RNase III in Escherichia coli also participates in pre-rRNA processing (King et al+, 1984), this result greatly influenced models for the evolutionary origins of the eukaryotic pre-rRNA processing machinery+ Cleavage at site A 0 also requires base pairing between the U3 snoRNA and the 59 ETS (Beltrame & Tollervey, 1995)+ We therefore investigated the relationship between U3 and Rnt1p+ In the course of this work we realized that a strain completely lacking Rnt1p is, in fact, able to efficiently cleave site A 0 + In contrast, cleavage in the 39 ETS is inhibited, as previously reported (Abou Elela et al+, 1996), although the sites of in vivo Rnt1p cleavage do not match the previously reported site of in vitro cleavage+…”
Section: Introductionmentioning
confidence: 99%
“…This genome organization resembles mostly the organization in plants, which also carry a cluster encoding for mixed C/D and H/ACA RNAs. In yeast, the clusters encode for only one type of snoRNA (6), and in metazoa such as mice, humans, and Drosophila, all snoRNAs are intronic, and each intron encodes for only a single snoRNA (9).…”
Section: Discussionmentioning
confidence: 99%
“…Most yeast snoRNAs are encoded by independent genes, some of which are found in clusters. However, seven intronic genes were also described (6). In plants, most snoRNAs are clustered and are independently transcribed, but intronic snoRNA gene clusters also exist (7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation